IMPLEMENTATION OF THE THREE READING SCHOOL LITERATION MOVEMENT MODEL TEN MINUTES FOR STUDENTS OF SMPN 14 PONTIANAK TIMUR - Dwi Artika (International Journal of Learning and Instruction (IJLI), 2023)
This research on the Application of the School Literacy Movement Model at SMPN 14 Pontianak Timur aims to describe the process of implementing the school literacy movement model, the constraints, and the supporting factors encountered at SMPN 14 Pontianak Timur. The research method used is descriptive qualitative with observation, interview and documentation techniques. The informants of this study consisted of 3 people, namely the school principal, deputy student affairs, and the coordinator of Al-Qur'an literacy activities. The results of this study are that there are 3 stages in the implementation of the School Literacy Movement activities at SMPN 14 Pontianak Timur. The first stage is habituation, students carry out reading activities of folklore books 30 minutes before learning begins and make the habit of reading the Qur'an for 15 minutes every 4th week for Muslim students. The second stage is learning, the teacher applies a discussion and question and answer system every hour the lesson takes place. The third stage is development, the school collaborates with the FIM organization (Indonesian Writing Forum) so that students can make short stories entitled Anthology of Pirate Ships, Anthology of Two Pairs of Sandals, Anthology of Small Notes from Finger Friends, and Anthology of Glasses published by Pustaka One . The obstacle to implementing the School Literacy Movement activities was that schools did not provide reading books so that students were asked to buy story books outside, even though not all students wanted or could afford to buy story books. The obstacle to implementing AlQur'an literacy activities is that there are still students who are not fluent and cannot read the Al-Qur'an. The supporting factors for the implementation of reading literacy activities and the implementation of Al-Qur'an literacy are the presence of teachers who support and assist schools in carrying out these activities.Keywords: application, model, school literacy movement